Maternal Psychological Aggression, Problem Behaviors, and the Mediating Roles of Psychological Resilience and Self-Control in Preschoolers - Qiao T; Wang X; Ye P (Psychology Research and Behavior Management)
Tianqi Qiao, Xinxin Wang, Pingzhi Ye College of Education, Guangzhou University, Guangzhou, People’s Republic of ChinaCorrespondence: Xinxin Wang; Pingzhi Ye, College of Education, Guangzhou University, Waihuan West Road 230, Panyu District, Guangzhou, 510006, People’s Republic of China, Email cynthia.wang@cynthia-edu.com; gzuyepingzhi@126.comObjective: This study examines the relationship between maternal psychological aggression (PA) and preschoolers’ problem behaviors (PB), focusing on the mediating roles of psychological resilience (PR) and self-control (SC), and gender differences.Methods: Mothers of 1141 preschoolers (52.9% boys, 47.1% girls; Mage = 4.26, SD = 0.85) participated in three waves of a longitudinal survey, each two months apart. Mothers participating in this study reported basic demographic information and PA at T1. PR and SC were reported at T2. PB of preschoolers was reported at T3. Path analysis models were employed to ascertain the relationship between PA and PB, as well as the mediating roles of PR and SC. Multiple group analyses were employed to ascertain the moderating role of gender.Results: Maternal PA (T1) was positively associated with preschoolers’ PB (T3) (β=0.220, p< 0.001). PR (T2) and SC (T2) independently and sequentially mediated the relationship between maternal PA (T1) and preschoolers’ PB (T3). Maternal PA (T1) was negatively associated with preschoolers’ PR (T2) only in boys (β =− 0.155, p< 0.001), not in girls (β =− 0.030, p> 0.05).Conclusion: This study reveals the impact and underlying mechanisms of maternal PA on preschoolers’ PB and highlights gender differences. These findings underscore the importance of protective factors in fostering positive adaptive behaviors in children subjected to maternal PA. Interventions should focus on preventing maternal PA and enhancing children’s PR and SC, particularly in boys, to promote healthy and positive behaviors.Keywords: psychological aggression, problem behavior, psychological resilience, self-control, preschoolers